Clean Energy Transitions in North Africa (OECD Publishing, 2020)
As the necessity of energy system transformation gathers pace at a global level, North African countries are increasingly making efforts towards their respective clean energy transitions. Clean energy transitions offer opportunities for North African countries to transform their energy infrastructure in ways that can meet the region's growing energy demand, create much-needed jobs and promote equitable socio-economic development, diversify their economies, and build climate change resilience, all while achieving low-carbon, sustainable, inclusive economic growth. Decarbonisation pathways are also instrumental for North African countries to achieve their climate and economic development ambitions. The region's long-term economic development and climate policy objectives, encompassed in countries' nationally determined contributions (NDCs) and the United Nations' Sustainable Development Goal (SDG) 7 and set out in the vision of the African Union's Agenda 2063, will require a transformation in how energy is supplied and consumed across the region